Tourism and Mobility. Best Practices and Conditions to Improve Urban Livability - La Rocca, Rosa Anna (TeMA - Journal of Land Use, Mobility and Environment, 2015)
This paper considers the relation between tourism and mobility and tries to highlight how tourism can act as a driving urban function in order to promote more sustainable lifestyles. Tourism and mobility are strictly connected: the moving from the usual residential place for leisure or entertainment represents the essential condition of tourism. There is no tourism without physical displacements, as the WTO definition affirms, highlighting that the movement of people is connected to two different mobility forms. On one hand, the tourist displacement is generated by the need to reach the destination (transit/access mobility). On the other hand, flows are generated by tourist activities at destination (visit, stay, entertainment, etc.) and it could be defined as an internal mobility. In both case, tourism represents a factor of human and environmental pressure. The WTO (2012) estimates that tourism mobility is responsible for 5% of CO2 emissions (referred to air travel) and points out that a change in the styles of tourism consumption is necessary also to meet the challenges of climate change that present cities must face. Traditionally, tourism and transport have been considered separately and mobility has been seen as a prerequisite rather than an integral part of the tourist activity; rarely this connection has been investigated in tourist planning and in mobility planning. The movements of visitors had a marginal role before the acknowledgment of the sustainable mobility paradigm, which introduced the concept of efficiency in transport system connected to the reduction of the environmental and social impacts encouraging modal shift in order to contrast the car-dependence. In the context of these considerations, this article tries to underline how tourism could play a strategic role in promoting sustainable way of moving inside the city if it will be mainstreamed within the government process of urban transformation. As a “pervasive” urban activity, tourism involves different sectors (public and private) and different social levels and it can act as an “accelerator of changing” to improve a new mobility culture and to change users behaviors. Which are the conditions needed to activate this change? This is the main question this paper tries to answer also considering some significant examples oriented to integrate tourism promotion with mobility planning.